Dental adhesive composition and kit
Patent Information
- Application Number
- JP2020212413
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-12-22
AI Technical Summary
【0017】 本発明の有機高分子系被膜強化剤は、特許文献1に記載された前記2液型歯科用接着性組成物を含めて揮発性有機溶媒としてエタノールを使用した場合であっても被膜強化剤として有効に機能する。そして、揮発性有機溶媒としてエタノールを使用し、更に本発明の有機高分子系被膜強化剤を含む本発明の歯科用接着性組成物は、安定して高い接着強度を発揮できるという特長を有する。さらに、本発明のキットは、本発明の歯科用接着性組成物の中でも、様々な歯科用材料に対する接着性に優れ且つ安定して高い接着強度を発揮できる歯科用接着性組成物を簡便に調製できるばかりでなく、長期間安定に保管できるという優れた特長を有する。
Smart Images

Figure 0007643680000001 
Figure 0007643680000002 
Figure 0007643680000003
Abstract
Description
[Technical field]
[0001] The present invention relates to Yes Machine polymer coating reinforcement Agent The present invention relates to a dental adhesive composition comprising the dental adhesive composition and a kit for preparing the dental adhesive composition. [Background technology]
[0002] In dental treatment, when filling a cavity after removing caries with a restorative material, it is necessary to adhere various materials to tooth structure. The types of restorative materials are diverse, such as composite resin, metal, zirconia, alumina, lithium disilicate glass, porcelain, etc. Conventionally, in order to adhere tooth structure or the restorative materials, it has been common to use an adhesive dedicated to each material, but dental adhesive compositions have also been developed that have excellent adhesion to various dental materials and provide good adhesive strength both to tooth structure and to silica-based ceramics.
[0003] That is, Patent Document 1 discloses a two-liquid dental adhesive composition that has excellent adhesion to various dental materials and can obtain good adhesive strength both to tooth substance and to silica-based ceramics, the two-liquid dental adhesive composition comprising a first part and a second part that are separately packaged from each other and that contains at least five components consisting of (A) an acidic group-containing polymerizable monomer, (B) a sulfur atom-containing polymerizable monomer, (C) a silane coupling agent, (D) a borate compound, and (E) water, the first part containing only the (A) acidic group-containing polymerizable monomer and the (B) sulfur atom-containing polymerizable monomer out of the five components, and the second part containing only the (C) silane coupling agent, the (D) borate compound, and the (E) water out of the five components.
[0004] Patent Document 1 explains the following about the two-component dental adhesive composition: (1) component (A) is an adhesive component for dentin, base metals, and zirconia ceramics, component (B) is an adhesive component for precious metals, and component (C) is an adhesive component for silica-based oxides; (2) component (E) water, in the presence of component (A), demineralizes the surface of dentin to improve adhesion to dentin and also has the function of improving adhesion to component (C) silica-based oxides and composite resin materials; (3) from the viewpoints of the storage stability of the first and second agents and the operability of the adhesive composition obtained by mixing the two agents (after mixing), it is preferable that both agents contain (F) a volatile organic solvent; and (4) in order to obtain a stable high adhesive strength, it is effective to incorporate a coating strengthening agent.
[0005] Here, the coating strengthening agent means an additive having a function of strengthening the coating formed when the dental adhesive composition is applied to the surface of a substrate. The above-mentioned coating is an adhesive layer interposed between the adherends (two objects to be bonded to each other), and if its strength is weak, the adhesive component may peel off from the adherend surface when air is blown to remove the solvent, or may be pushed out and disturbed by pressure during bonding, resulting in poor adhesion. However, the use of a coating strengthening agent can suppress the occurrence of such a phenomenon. In the two-liquid dental adhesive composition, it is said that resin materials such as polymethyl methacrylate (PMMA) resin, inorganic fillers such as silica particles, silica-zirconia particles, quartz, and fluoroaluminosilicate glass, particles (organic fillers) made of organic polymers such as polymethyl methacrylate, polymethyl methacrylate-polyethyl methacrylate copolymer, ethylene-vinyl acetate copolymer, and styrene-butadiene copolymer can be used as coating strengthening agents, and dental adhesives using poly(lower (meth)acrylate) are also known (see Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-27913 A [Patent Document 2] Patent No. 5808447 [Patent Document 3] Special Publication No. 2013-515775 [Patent Document 4] Patent No. 5395362 [Patent Document 5] Patent No. 3664425 Summary of the Invention [Problem to be solved by the invention]
[0007] As mentioned above, Patent Document 1 explains that it is effective to add a film strengthening agent to obtain stable and high adhesive strength, but only lists examples of usable film strengthening agents, and does not conduct detailed studies. Therefore, the present inventors have verified the effect of adding a film strengthening agent, and have found that in a system containing an optional component (F) volatile organic solvent, the desired effect may not be obtained depending on the type of organic solvent used. Specifically, when ethanol is used as the component (F), it has been found that a sufficient effect may not be obtained even if the film strengthening agent exemplified in Patent Document 1 is added. Ethanol is an organic solvent that is relatively widely used in dental adhesive compositions, and its frequency of use tends to increase due to its high safety, and the inability to strengthen the film in a system containing ethanol is a major constraint in product design.
[0008] Therefore, the present invention aims to provide a coating strengthening agent that functions effectively even when ethanol is used as a (volatile) organic solvent, including the two-component dental adhesive composition described in Patent Document 1, and by extension, to provide a dental adhesive composition that uses ethanol as an organic solvent and achieves a stable high adhesive strength. [Means for solving the problem]
[0009] The present invention is to solve the above problems, and a first aspect of the present invention is a polymerizable monomer containing an acidic group-containing polymerizable monomer. Ingredients: 100 parts by mass ,water : 5 to 30 parts by mass, ethanol: 10 to 295 parts by mass, and The -OH groups in the cellulose molecule are the groups: -OR and / or -OC(=O)-R (wherein R in these groups is An alkyl group having 1 to 5 carbon atoms. .) was replaced by Alkyl cellulose in The organic polymer-based coating reinforcement agent is made of a cellulose derivative having a solubility in water of 0.1 (g / 100 g-solvent) or less and a solubility in ethanol of 1 (g / 100 g-solvent) or more at 25°C. A dental adhesive composition comprising 0.05 to 3 parts by mass of It is.
[0010] The above form Dental adhesive composition (hereinafter, "the present invention" Dental adhesive composition " and (also called.) The organic polymer-based coating reinforcement agent (hereinafter, the organic polymer-based coating reinforcement agent is also referred to as "the organic polymer-based coating reinforcement agent of the present invention" or "the coating reinforcement agent of the present invention") The above Alkyl cellulose but It is preferable that the polymer compound or polymer composition has a molecular weight distribution in which the content of components having a molecular weight of 140,000 or more is 20% or more.
[0013] The dental adhesive composition in the above form (hereinafter also referred to as "dental adhesive composition of the present invention") preferably further contains 0.5 to 20 parts by mass of a silane coupling agent and / or 1 to 50 parts by mass of an inorganic coating reinforcing agent.
[0014] Further, the dental adhesive composition of the present invention comprises 100 parts by mass of a polymerizable monomer component (A) consisting of an acidic group-containing polymerizable monomer (a1) and an acidic group-free polymerizable monomer (a2), 0.5 to 20 parts by mass of a silane coupling agent (B), 5 to 30 parts by mass of water (c1), and 10 to 295 parts by mass of ethanol (c2), as a solvent component (C): 3 0~ 25 0 parts by mass, The alkyl cellulose is an alkyl cellulose in which the -OH groups in the cellulose molecule are replaced by groups: -OR and / or -OC(=O)-R (wherein R in these groups is an alkyl group having 1 to 5 carbon atoms), and has a solubility in water of 0.1 (g / 100 g-solvent) or less and a solubility in ethanol of 1 (g / 100 g-solvent) or more at 25°C.It is particularly preferable that the composition contains 0.05 to 53 parts by mass of a coating reinforcement agent (D) including 0.05 to 3 parts by mass of an organic polymer coating reinforcement agent (d1), and 0.01 to 20 parts by mass of a polymerization initiator (E) composed of a single or multiple components.
[0015] The present invention two The form of the present invention is a kit having a first agent and a second agent packaged separately from each other, and by mixing these two agents, the above-mentioned particularly preferred dental adhesive composition of the present invention can be prepared. The first agent and the second agent are each prepared based on the composition of the dental adhesive composition to be prepared, by mixing each of the components specified in the composition in the following (1) to ( 4 The kit is characterized in that it comprises a first composition and a second composition having compositions determined by dividing the first composition and the second composition so as to satisfy the conditions shown in Ingredient classification criteria: (1) The polymerizable monomer component (A) is contained only in the first part. (2) The silane coupling agent (B) is contained only in the second part. (3) Regarding the solvent component (C), the ethanol (c2) is contained only in the second part or in both the first and second parts, and other components are contained in the first and / or second parts. (4) The dental organic polymer-based coating strengthening agent (d1) is contained in either one or both of the first and second agents.
[0016] In the kit of the above form (hereinafter also referred to as "the kit of the present invention"), it is preferable that the dental adhesive composition to be prepared further contains 1 to 50 parts by mass of an inorganic coating reinforcement agent (d2) as the coating reinforcement agent (D), and that the inorganic coating reinforcement agent (d2) is contained only in the first agent. Effect of the Invention
[0017] The organic polymer-based coating strengthening agent of the present invention effectively functions as a coating strengthening agent even when ethanol is used as a volatile organic solvent, including the two-liquid dental adhesive composition described in Patent Document 1. The dental adhesive composition of the present invention, which uses ethanol as a volatile organic solvent and further contains the organic polymer-based coating strengthening agent of the present invention, has the characteristic of being able to stably exhibit high adhesive strength. Furthermore, the kit of the present invention not only allows easy preparation of a dental adhesive composition that has excellent adhesiveness to various dental materials and can stably exhibit high adhesive strength among the dental adhesive compositions of the present invention, but also has the excellent characteristic of being able to be stored stably for a long period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The organic polymer-based coating strengthening agent of the present invention comprises a polymerizable monomer containing an acidic group-containing polymerizable monomer, water, and a volatile organic solvent. Ethanol as The present invention solves the above-mentioned problems specific to dental adhesive compositions comprising the above-mentioned compound, which has a solubility in water of 0.1 (g / 100 g-solvent) or less, ethanol It is made of a cellulose derivative having a solubility of 1 (g / 100g-solvent) or more in 。
[0019] Here, the organic polymer-based film strengthening agent means an organic additive that is mixed in a small amount (usually 10 parts by mass or less per 100 parts by mass of the polymerizable monomer) with a dental adhesive composition containing a polymerizable monomer containing an acidic group-containing polymerizable monomer, water, and a volatile organic solvent, thereby improving the strength of the film formed when the organic solvent is removed during application of the dental adhesive composition. Also, the cellulose derivative means a polymer compound in which the -OH group in the cellulose molecule is replaced by a group: -OR and / or a group: -OC(=O)-R (wherein R in these groups means a monovalent organic group).
[0020] Cellulose derivatives having the above-mentioned solubility are commercially available and are materials used in the dental field. However, their specific uses are as viscosity adjusters for temporary (dental) cements (see Patent Document 3), colloid protectors for dental primer compositions made of metal colloid solutions (see Patent Document 4), and main components of dental surface coating materials suitable for reducing polymerization inhibition during hardening of radical polymerizable compositions such as dental resin cements (see Patent Document 5), and none of these agents or materials contain acidic group-containing polymerizable monomers, nor do they form an adhesive layer between two types of adherends. As shown in the above Patent Documents 1 and 2, known coating reinforcers for dental adhesive compositions containing a polymerizable monomer containing an acidic group-containing polymerizable monomer, water and a volatile organic solvent include poly(meth)acrylate-based resins containing poly(lower (meth)acrylate), ethylene-vinyl acetate copolymers, styrene-butadiene copolymers, silica particles, silica-zirconia particles, quartz, fluoroaluminosilicate glass, etc., but as far as the present inventors know, there are no examples of using a cellulose derivative as a coating reinforcer for the dental adhesive composition. And it has been confirmed for the first time that the cellulose derivative functions as a coating reinforcer that solves the above problems specific to dental adhesive compositions.
[0021] The organic polymer-based coating reinforcing agent of the present invention, the dental adhesive composition of the present invention, and the kit of the present invention will be described in detail below. In this specification, unless otherwise specified, the expression "x to y" using the numerical values x and y means "x or more and y or less". In such an expression, when a unit is added only to the numerical value y, the unit is also applied to the numerical value x. In addition, in this specification, the term "(meth)acrylic" means both "acrylic" and "methacrylic". Similarly, the term "(meth)acrylate" means both "acrylate" and "methacrylate", and the term "(meth)acryloyl" means both "acryloyl" and "methacryloyl".
[0022] 1. The organic polymer-based coating strengthening agent of the present invention The organic polymer-based coating strengthening agent of the present invention is an organic polymer-based coating strengthening agent for a dental adhesive composition, which contains a polymerizable monomer containing an acidic group-containing polymerizable monomer, water, and a volatile organic solvent, and has a solubility in water at 25°C of 0.1 (g / 100 g-solvent) or less; ethanol It is characterized by being made of a cellulose derivative with a solubility in ethanol of 1 (g / 100g-solvent) or more. Because of its high solubility in ethanol, it is possible to strengthen the coating even in agents that use ethanol as a volatile organic solvent, and because of its low solubility in water, it is possible to quickly remove the water without swelling after the volatile organic solvent is removed by air blowing.
[0023] Here, the cellulose derivative is a cellulose derivative in which the -OH group in the cellulose molecule is replaced with the group: -OR and / or the group: -OC(=O)-R (wherein R in these groups is It is an alkyl group having 1 to 5 carbon atoms. Compounds substituted with 1) Alkyl cellulose Since cellulose itself is a polymer compound having a molecular weight distribution, cellulose derivatives are also polymer compounds having a molecular weight distribution.
[0024] The -R in the group replacing the -OH group in the cellulose molecule is a methyl group, an ethyl group, a propyl group, Moto etc. Examples include: Such alkyl cellulose in which R is an alkyl group having 1 to 5 carbon atoms is It is more preferable to use alkyl cellulose in which R is an alkyl group having 1 to 5 carbon atoms, particularly ethyl cellulose, because the hydrophilicity is not too high and therefore water can be easily removed by air blowing, and a strong coating can be formed.
[0025] It is known that the properties of cellulose derivatives depend on the degree of polymerization of the cellulose itself (corresponding to the molecular weight distribution of the cellulose derivative), the degree of substitution, the distribution of substituents, etc., and it is believed that the solubility in various solvents is also affected by these factors, but for commercially available cellulose derivatives, these analytical values are often unknown. According to the studies of the present inventors, the solubility in water is 0.1 (g / 100 g-solvent) or less, and the solubility in the volatile organic solvent is 1 (g / 100 g-solvent) or more. The above Cellulose Derivatives (Alkyl cellulose) It has been confirmed that such a compound effectively functions as a film strengthening agent for dental adhesive compositions containing volatile organic solvents, including ethanol, that are commonly used in dental adhesive compositions.
[0026] From the viewpoint of the film strengthening effect for dental adhesive compositions using ethanol as a volatile solvent, the cellulose derivative used has a solubility in ethanol of 1 (g / 100g-ethanol) or more. Note that the solubility depends on the molecular weight, and if the cellulose derivative contains too high a content of components with extremely low molecular weight, the film strengthening effect is thought to decrease. For the reasons that the dental hardenable composition containing the organic polymer-based film strengthening agent of the present invention has a suitable fluidity and can be applied uniformly, and that a good film can be formed after application and air blowing to remove the volatile organic solvent, it is preferable to use a polymer compound or polymer composition having a molecular weight distribution in which the content ratio of components with molecular weights of 140,000 or more is 20% or more as the cellulose derivative.
[0027] The molecular weight and its distribution of the organic polymer coating strengthener can be measured by gel permeation chromatography (GPC) or advanced polymer chromatography (APC). In addition, a polystyrene standard, for example, AQCUITY APC Polystylene Middle MW Calibration Kit (Waters) can be used as a standard substance for the measurement. In addition, the solvent used in this case is preferably tetrahydrofuran in terms of the solubility of both the standard substance and the organic polymer coating strengthener.
[0028] 2. Dental adhesive composition of the present invention The dental adhesive composition of the present invention is characterized by containing 100 parts by mass of a polymerizable monomer consisting of an acidic group-containing polymerizable monomer and an acidic group-free polymerizable monomer, 5 to 30 parts by mass of water, 10 to 295 parts by mass of ethanol, and 0.05 to 3 parts by mass of the organic polymer-based coating strengthening agent of the present invention.
[0029] The dental adhesive composition of the present invention is particularly preferably a dental adhesive composition (hereinafter also referred to as "the dental adhesive composition containing a silane coupling agent of the present invention") that contains 100 parts by mass of a polymerizable monomer component (A) consisting of an acidic group-containing polymerizable monomer (a1) and an acidic group-free polymerizable monomer (a2), 0.5 to 20 parts by mass of a silane coupling agent (B), 20 to 250 parts by mass of a solvent component (C) containing 5 to 30 parts by mass of water (c1) and 10 to 295 parts by mass of ethanol (c2), 0.05 to 53 parts by mass of a coating reinforcer (D) containing 0.05 to 3 parts by mass of an organic polymer coating reinforcer (d1) of the present invention, and 0.01 to 20 parts by mass of a polymerization initiator (E) consisting of a single or multiple components, because the dental adhesive composition of the present invention uses ethanol, which is highly safe, as a volatile organic solvent, and has excellent adhesion to various dental materials and can stably exhibit high adhesive strength.
[0030] The dental adhesive composition of the present invention, particularly the dental adhesive composition containing a silane coupling agent of the present invention, can be used for adhesion to various objects to be adhered. Specifically, it can be used for adhesion to various dental materials such as ceramics such as zirconia ceramics and silica-based ceramics (porcelain, etc.), tooth structure (dentin, enamel), base metals containing iron, nickel, chromium, cobalt, tin, aluminum, copper, titanium, etc. as main components, and resin hardened bodies (hard resin teeth, hybrid resins, CAD / CAM resin blocks) containing dispersed fillers such as silica particles or silica-zirconia particles.
[0031] In dental adhesive compositions of the present invention other than the dental adhesive composition containing a silane coupling agent of the present invention, the blending of the acidic group-free polymerizable monomer (a2) and the polymerization initiator (E) is optional, and apart from this point, there is no particular difference from the dental adhesive composition containing a silane coupling agent of the present invention. Therefore, the dental adhesive composition of the present invention will be described in detail below using the dental adhesive composition containing a silane coupling agent of the present invention as an example.
[0032] (1) Polymerizable monomer component (A) The polymerizable monomer (A) is a polymerizable monomer component containing an acidic group-containing polymerizable monomer, and in the silane coupling agent-containing dental adhesive composition of the present invention, it is composed of an acidic group-containing polymerizable monomer (hereinafter also referred to as "acid monomer") (a1) and an acidic group-free polymerizable monomer (hereinafter also referred to as "non-acid monomer") (a2). The acid monomer (a1) and the non-acid monomer (a2) are not particularly different from those in conventional dental adhesive compositions, and those used in conventional dental adhesive compositions can be used without any particular restrictions.
[0033] From the viewpoints of adhesion and storage stability, the content of the acid monomer (a1) in the polymerizable monomer component (A) is preferably in the range of 1 to 60 parts by mass, and more preferably in the range of 5 to 30 parts by mass, when the total mass of the (A) component is taken as 100 parts by mass. The content of the non-acid monomer (a2) is the amount obtained by subtracting the content of the acid monomer (a1) from 100 parts by mass.
[0034] (1-1) Acidic Group-Containing Polymerizable Monomer (a1) (a1): The acidic group-containing polymerizable monomer (acid monomer) refers to a compound having one or more acidic groups, such as phosphinico group {=P(=O)OH}, phosphono group {-P(=O)(OH)2}, carboxyl group {-C(=O)OH}, dihydrogen phosphate monoester group {-OP(=O)(OH)2}, hydrogen phosphate diester group {(-O-)2P(=O)OH}, sulfo group (-SO3H), and acid anhydride skeleton {-C(=O)-OC(=O)-}, and a polymerizable unsaturated group in the molecule. The acid monomer (a1) functions as an adhesive component for teeth, base metals, and zirconia ceramics, as in the two-liquid dental adhesive composition described in the above-mentioned Patent Document 1. Compounds having a carboxyl group, a dihydrogen phosphate monoester group, or a hydrogen phosphate diester group as an acidic group are preferred, as they have high stability against water and can slowly dissolve the smear layer on the tooth surface and slowly demineralize the teeth, and compounds having a dihydrogen phosphate monoester group and / or a hydrogen phosphate diester group are most preferred.
[0035] Examples of acid monomers that can be suitably used include those having a dihydrogen phosphate monoester group or a hydrogen phosphate diester group, such as 2-(meth)acryloyloxyethyl dihydrogen phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 6-(meth)acryloyloxyhexylphenyl hydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 1,3-di(meth)acryloylpropane-2-dihydrogen phosphate, 1,3-di(meth)acryloylpropane-2-phenyl hydrogen phosphate, and bis[5-{2-(meth)acryloyloxyethoxycarbonyl}heptyl]hydrogen phosphate. Examples of acid monomers having a carboxyl group include acrylic acid, methacrylic acid, 4-(meth)acryloxyethyltrimellitic acid, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, 1,4-di(meth)acryloyloxypyromellitic acid, 2-(meth)acryloyloxyethylmaleic acid, 2-(meth)acryloyloxyethylphthalic acid, and 2-(meth)acryloyloxyethylhexahydrophthalic acid. vinegar Examples of acid monomers having a sulfo group include 2-methacrylamide-2-methylpropanesulfonic acid, 2-acrylamide-2-methylpropanesulfonic acid, p-vinylbenzenesulfonic acid, vinylsulfonic acid, etc. These acid monomers can be used alone or in combination.
[0036] (1-2) Acidic group-containing non-polymerizable monomer (a2) (a2): non-polymerizable monomer containing an acidic group (non-acid monomer) means a compound having no acidic group in the molecule and having at least one polymerizable unsaturated group. The non-acid monomer (a2) mainly functions as a base component for forming the adhesive layer.
[0037] Examples of non-acid monomers that can be suitably used include monofunctional polymerizable monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, glycidyl (meth)acrylate, 2-cyanomethyl (meth)acrylate, benzyl methacrylate, polyethylene glycol mono(meth)acrylate, allyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and glyceryl mono(meth)acrylate; ethylene glycol di(meth)acrylate, diethylene Glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, 2,2'-bis[4-(meth)acryloyloxyethoxyphenyl]propane, 2,2'-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane, 2,2'-bis[4-(meth)acryloyloxyethoxyethoxyethoxyphenyl]propane, 2,2'-bis[4-(meth)acryloyloxyethoxyethoxyethoxyethoxyphenyl]propane, 2,2'-bis{4 -[2-hydroxy-3-(meth)acryloyloxypropoxy]phenyl}propane, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-bis(methacrylethyloxycarbonylamino)-2,2,4-trimethylhexane, 1,6-bis(methacrylethyloxycarbonylamino)-2,4,4-trimethylhexane, urea Examples of the polymerizable monomer include polyfunctional polymerizable monomers such as ethane (meth)acrylate, epoxy (meth)acrylate, trimethylolpropane trimethacrylate, and pentaerythritol tetramethacrylate; fumarate ester compounds such as monomethyl fumarate, diethyl fumarate, and diphenyl fumarate; styrene and α-methylstyrene derivatives such as styrene, divinylbenzene, α-methylstyrene, and α-methylstyrene dimer; and allyl compounds such as diallyl phthalate, diallyl terephthalate, diallyl carbonate, and allyl diglycol carbonate.These non-acid monomers may be used alone or in combination.
[0038] In order to improve adhesion to precious metals, a sulfur atom-containing polymerizable monomer such as 6-methacryloyloxyhexyl-2-thiouracil-5-carboxylate or 2-(11-methacryloyloxyundecylthio)-5-mercapto-1,3,4-thiadiazole may be blended as the non-acid monomer (a2) in an amount of about 0.01 to 10 parts by mass per 100 parts by mass of the total mass of the component (A).
[0039] (2) Silane coupling agent (B) The silane coupling agent (B) functions as an adhesive component for silica-based ceramics, similarly to the two-component dental adhesive composition described in Patent Document 1, and any silane coupling agent that is known to be usable in the above-mentioned two-component dental adhesive composition can be used without any particular restrictions.
[0040] From the viewpoint of adhesion and handling, the silane coupling agent having a polymerizable group is preferably used.Specific examples of the silane coupling agent having a polymerizable group that is preferably used include γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl tri(trimethylsiloxy)silane, γ-methacryloxypropyl triethoxysilane, γ-methacryloxypropyl methyldiethoxysilane, γ-methacryloxypropyl triisopropoxysilane, γ-methacryloxypropyl trimethoxysilane, methacryloxypropyl triallylsilane, etc.
[0041] The amount of the silane coupling agent (B) added is usually 0.5 to 20 parts by mass, and preferably 1 to 10 parts by mass, per 100 parts by mass of the polymerizable monomer component (A).
[0042] (3) Solvent component (C) The solvent component (C) contains water (c1) and ethanol (c2), and may contain a volatile organic solvent other than ethanol (hereinafter also referred to as "other solvent") (c3) as necessary. Water (c1) has the function of promoting the demineralization action of the acid monomer (a1), and ethanol (c2) and other volatile organic solvents (c3) play the role of a diluent for uniform application of the adhesive and as a component for promoting the penetration of the adhesive components into the tooth structure. As the other solvent (c3), acetone, methyl ethyl ketone, isopropyl alcohol, t-butyl alcohol, dimethoxyethane, etc. can be suitably used.
[0043] The content of the solvent component (C) relative to 100 parts by mass of the polymerizable monomer component (A) is 3 The amount of water (c1), ethanol (c2) and other solvents (c3) blended relative to 100 parts by mass of the polymerizable monomer component (A) is, respectively, 5 to 30 parts by mass for (c1), 10 to 295 parts by mass for (c2) and 0 to 285 parts by mass for (c3), and preferably 7 to 20 parts by mass for (c1), 15 to 245 parts by mass for (c2) and 0 to 235 parts by mass for (c3). The proportion of ethanol (c2) in the entire solvent component (C) is preferably 35% by mass or more.
[0044] (4) Coating strengthener (D) The coating reinforcing agent (D) contains the organic polymer coating reinforcing agent (d1) of the present invention, and may contain an inorganic coating reinforcing agent (d2) as necessary. As the inorganic coating reinforcing agent (d2), silica particles, silica-zirconia particles, quartz, fluoroaluminosilicate glass, aluminum oxide, etc. are preferably used.
[0045] The content of the coating reinforcement agent (D) is 0.05 to 53 parts by mass, and the content of the organic polymer coating reinforcement agent (d1) of the present invention is 0.05 to 3 parts by mass per 100 parts by mass of the polymerizable monomer component (A). If the content of (d1) is less than 0.05 parts by mass, a good coating cannot be formed. If it exceeds 3 parts by mass, the viscosity of the adhesive composition before air blowing becomes too high, and it cannot be uniformly applied to the adherend. If an inorganic coating reinforcement agent (d2) is included, the content of (d2) is preferably 1 to 50 parts by mass per 100 parts by mass of the polymerizable monomer component (A).
[0046] (5) Polymerization initiator (E) The polymerization initiator (E) has the function of increasing adhesive strength by polymerizing and curing the polymerizable monomer component (A) that has penetrated into the tooth substance as the adherend. As the polymerization initiator (E), any one that can be used in a dental adhesive composition, for example, a polymerization initiator composed of a single or multiple components that can be used in a two-part dental adhesive composition described in the above-mentioned Patent Document 1, can be used without any particular limitation. As the polymerization initiator (E), it is preferable to use a photopolymerization initiator or a chemical polymerization initiator.
[0047] Examples of suitable photopolymerization initiators include camphorquinone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide. These photopolymerization initiators can also be used in combination with a photopolymerization accelerator. Examples of suitable photopolymerization accelerators include ethyl p-dimethylaminobenzoate, N,N-diethylaniline, and 4-dimethylaminopyridine.
[0048] As the chemical polymerization initiator, organic peroxides, amines, aryl borate compounds, thiourea compounds, transition metal compounds, etc. can be used alone or in appropriate combination. Examples of organic peroxides include t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-butylperoxy-3,5,5-trimethylhexanoate, and t-butylperoxybenzoate. Examples of amines include N-methyl-p-toluidine, N,N-diethylaniline, N,N-dimethyl-p-toluidine, p-dimethylaminobenzoic acid, ethyl p-dimethylaminobenzoate, triethylamine, and N,N-dimethylaminoethyl (meth)acrylate. Examples of arylborate compounds include sodium salt of tetraphenylboron, triethanolamine salt of tetraphenylboron, sodium salt of tetrakis(p-fluorophenyl)boron, triethanolamine salt of tetrakis(p-fluorophenyl)boron, sodium salt of tetrakis(3,5-bistrifluoromethyl)phenylboron, and sodium salt of tetrakis(3,5-bis(trifluoromethyl)phenylboron). Examples of suitable compounds include triethanolamine salts of tetrakis(3,5-bistrifluoromethyl)phenylborane and phosphonium ion salts of tetrakis(3,5-bistrifluoromethyl)phenylborane; examples of suitable thiourea compounds include N,N'-ethylenethiourea, N-benzoylthiourea, N,N'-dimethylthiourea, 1-(2-pyridyl)-2-thiourea, and 1-acetyl-2-thiourea; examples of suitable transition metal compounds include titanium(IV) tetraisopropoxide, vanadyl oxide acetylacetonate(IV), vanadyl oxalate(IV), bis(maltolato)oxovanadium(IV), manganese(II) acetate, iron(II) acetate, iron(III) acetate, cobalt(II) acetate, cobalt(III) trisacetylacetonate, nickel(II) chloride, nickel(III) acetylacetonate, copper(II) chloride, copper(II) acetate, copper(II) acetylacetonate, and zinc(II) acetate.
[0049] (6) Other ingredients The dental adhesive composition of the present invention may contain, in addition to the components (A) to (E), components such as a polymerization inhibitor, a polymerization accelerator, a pigment, a polymer other than the component (D), a fungicide, and an antibacterial agent, provided that the curing of the present invention is not impaired.
[0050] 3. Kits of the Present Invention From the viewpoint of storage stability, the dental adhesive composition containing a silane coupling agent of the present invention is preferably used as a kit in which the first agent and the second agent are packaged separately. That is, the kit of the present invention is stored as a package in which each component (A) to (E) of the dental adhesive composition containing a silane coupling agent of the present invention, which is the preparation target, is divided into two compositions (the first composition and the second composition) without combination so as to satisfy the conditions for stable storage of each composition, and the kit is designed to prepare the dental adhesive composition containing a silane coupling agent of the present invention by opening both packages at the time of use and mixing the first composition and the second composition, which are the contents.
[0051] Here, the conditions that must be satisfied when dividing each of the above components are: (1) the polymerizable monomer component (A) is contained only in the first agent; (2) the silane coupling agent (B) is contained only in the second agent; (3) with respect to the solvent component (C), the ethanol (c2) is contained only in the second agent or in both the first and second agents, and the other components are contained in the first agent and / or the second agent; and (4) the organic polymer-based coating strengthening agent (d1) is contained in either or both of the first agent and the second agent.
[0052] In addition, water (c1) which becomes the solvent component (C) and other organic solvents which are blended as necessary can be blended in either one or both of the first and second agents, respectively, but it is preferable that the second agent contains water (c1) and ethanol (c2). In addition, the polymerization initiator (E) may be blended separately into either one or both of the first composition and the second composition depending on the polymerization initiator actually used so that the polymerization of the polymerizable monomer component (A) does not occur during storage. For example, when the polymerization initiator is a chemical polymerization initiator consisting of a single component, it may be blended only into the second composition, and when the polymerization initiator is a chemical polymerization initiator consisting of a combination of multiple components, all the components may be blended only into the second composition, or the components may be blended appropriately into the first composition and the second composition so that they do not coexist with the polymerizable monomer component (A) in a state showing polymerization activity. When the polymerization initiator is a photopolymerization initiator, in principle, it may be blended into either composition as long as it is stored in a light-shielded state. However, similar to the case of a chemical polymerization initiator, it is preferable that it does not coexist with the polymerizable monomer component (A) in a state that exhibits polymerization activity when irradiated with light.
[0053] Furthermore, like the two-liquid dental adhesive composition described in Patent Document 1, when the silane coupling agent-containing dental adhesive composition of the present invention, which is the preparation target, contains a sulfur atom-containing polymerizable monomer as the polymerizable monomer component (A) and further contains a borate compound that also functions as a component of the polymerization initiator, it is preferable to mix the borate compound only in the second composition. In this case, when the polymerization initiator (E) contains an organic peroxide, the organic peroxide and the sulfur atom-containing polymerizable monomer may react during storage to cause gelation, so it is preferable to mix the organic peroxide only in the second composition.
[0054] The specific compositions of the first composition and the second composition may be determined based on the silane coupling agent-containing dental adhesive composition of the present invention, which is the object of preparation, by dividing each component into either the first composition, the second composition, or both, so as to satisfy the above-mentioned conditions. EXAMPLES
[0055] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0056] 1. The abbreviations of the substances used in the examples and comparative examples are explained below. (1) a1: Acidic group-containing polymerizable monomer (acid monomer) ·MDP: 10-methacryloxydecyl dihydrogen phosphate · AET: 4-Acryloyloxyethyl trimellitate.
[0057] (2) a2: Polymerizable monomer not containing an acidic group (non-acid monomer) HEMA: 2-hydroxyethyl methacrylate BisGMA: Bisphenol A di(2-hydroxypropoxy) dimethacrylate ·UDMA: Di(methacryloyloxy)-2,2,4-trimethylhexamethylenediurethane ·3G: Triethylene glycol dimethacrylate.
[0058] (3) B: Silane coupling agent ·SC1: γ-Methacryloxypropyltriethoxysilane ·SC2: γ-Methacryloxypropyltriisopropoxysilane · SC3: Methacryloxypropyltriallylsilane.
[0059] (4) d1: Coating strengthening agent of the present invention EC1: Ethyl cellulose (content of components with molecular weight of 140,000 or more: 24.6%, solubility: 0.1g / 100g water or less, 1g / 100g ethanol or more, manufactured by Wako Pure Chemical Industries, Ltd.) EC2: Ethyl cellulose (content of components with molecular weight of 140,000 or more: 16.2%, solubility: 0.1g / 100g water or less, 1g / 100g ethanol or more, manufactured by Wako Pure Chemical Industries, Ltd.) The above molecular weight distribution and the molecular weight distributions of HPC1 and HPC2 described below are based on the results of measurements using a Waters Advanced Polymer Chromatography system (column: two connected AQUITY APC XT 45 1.7 μm columns, standard substance: ACQUITY APC Polystylene Middle MW Calibration Kit, solvent: tetrahydrofuran).
[0060] (5) d2: Inorganic coating strengthening agent · DM-30: Average primary particle size of 7 nm, silica particles treated with dimethyldichlorosilane (manufactured by Tokuyama Corporation).
[0061] (6) d3: Organic polymer coating strengthening agent other than d1 HPC1: Hydroxypropyl cellulose (content of components with molecular weight of 140,000 or more: 42.0%, solubility: 5g / 100g water or more, 1g / 100g ethanol or more, manufactured by Wako Pure Chemical Industries, Ltd.) HPC2: Hydroxypropylcellulose (content of components with molecular weight of 140,000 or more: 32.3%, solubility: 5g / 100g water or more, 1g / 100g ethanol or more, manufactured by Wako Pure Chemical Industries, Ltd.) PMMA: Polymethyl methacrylate (weight average molecular weight 1,000,000, solubility: 0.1g / 100g water or less, 0.1g / 100g ethanol or less).
[0062] (7) E: Polymerization initiator CQ: Camphorquinone DMBE: p-Dimethylaminobenzoic acid ethyl ester V1: Bis(maltolato)oxovanadium(IV) ·V2: Vanadyl oxalate V3: Vanadium oxide acetylacetonate Cu1: Copper(II) acetate Cu2: Copper(II) acetylacetonate PO1: t-Butyl hydroperoxide PO2: 1,1,3,3-tetramethylbutyl hydroperoxide PO3: t-Butylperoxy-3,5,5-trimethylhexanoate PO4: t-Butyl peroxybenzoate B1: Triethanolamine salt of tetraphenylboron B2: Sodium salt of tetraphenylboron ·TU1: N-benzoylthiourea ·TU2: N,N'-Ethylenethiourea.
[0063] 2. Evaluation methods for dental adhesives The dental adhesives prepared in the Examples and Comparative Examples were evaluated for adhesion and coating properties. The evaluation methods are described below.
[0064] (1) Adhesion evaluation The adhesive properties of dental adhesives were evaluated by conducting initial adhesion tests and adhesion durability tests for each of the following systems: (1) tooth substance and composite resin when used to bond the tooth substance / composite resin system (tooth substance / CR system) and (2) porcelain porcelain and resin cement when used to bond the porcelain porcelain / resin cement system (P porcelain / R cement system), and evaluating the adhesive strength at that time. At this time, air was blown under stronger pressure than usual.
[0065] To investigate storage stability, the above evaluation was performed on the composition immediately after preparation, and on the composition stored at 50° C. for 2 weeks after preparation, both of which were used as adhesives. The evaluation method is described in detail below.
[0066] (1-1) Method for preparing evaluation samples 1) Preparation of samples for measuring tooth / CR adhesive strength: A cow's front teeth extracted within 24 hours after slaughter were ground with water-resistant abrasive paper P600 under water, and the dentin plane was scraped off to be parallel and flat to the labial surface to prepare an adherend. Next, a double-sided tape with a 3 mm diameter hole was attached to the ground surface of each of these two types of adherends. Next, the dental adhesive prepared in each Example and Comparative Example was applied to the adhesive surface exposed from the hole of the double-sided tape on the ground surface, and dried by air blowing under high pressure conditions for 5 seconds. The high pressure conditions in this case refer to a pressure of 0.2 MPa and a distance of 5 cm from the air blow nozzle to the adherend surface. In normal adhesion tests, the pressure is 0.2 MPa and the distance is 8 cm.
[0067] A 0.5 mm thick paraffin wax with a hole of 8 mm in diameter was attached to the adhesive surface coated with dental adhesive so that the hole in the paraffin wax and the hole in the double-sided tape were concentric to create a simulated cavity. This simulated cavity was filled with dental composite resin (Estelite Σ Quick, manufactured by Tokuyama Dental Co., Ltd.) and lightly pressed with polyester film, and then photocured by irradiating light for 10 seconds using a visible light irradiator (Elipar, manufactured by 3MESPE Co., Ltd.). Then, a pre-polished SUS304 round bar (diameter 8 mm, height 18 mm) was bonded with resin cement (Bistite II, manufactured by Tokuyama Dental Co., Ltd.) to prepare an evaluation sample. The composite resin used was a photopolymerizable composition containing camphorquinone and an amine compound.
[0068] 2) Preparation of a sample for measuring the adhesive strength of P porcelain / R cement system: As an adherend, "Noritake Super Porcelain AAA" (Kuraray Noritake Co., Ltd., length 15 mm x width 15 mm x thickness 3 mm), which is a dental ceramic (so-called porcelain) made of silica-based crystallized glass, was used, and one side of this adherend was polished with #800 waterproof abrasive paper. Then, a double-sided tape with a hole of 3 mm in diameter was attached to the polished surface of the adherend. Next, the dental composition of each Example and each Comparative Example was applied with a microbrush to the adhesive surface exposed from the hole of the double-sided tape on the polished surface, and the dental composition applied to the adhesive surface was dried by air blowing for 5 seconds. Then, a previously polished SUS304 round bar (diameter 8 mm, height 18 mm) was bonded with resin cement (RelyX Ultimate Resin Cement, 3MESPE Co., Ltd.) to prepare an evaluation sample. The resin cement used (RelyX Ultimate Resin Cement, manufactured by 3MESPE) is a chemically polymerizable composition.
[0069] (1-2) Evaluation method for initial adhesive strength and adhesive durability The samples prepared as described above were divided into two test groups for each Example or Comparative Example, and for one of the test groups, each sample was immersed in water at 37°C for 24 hours, and then the tensile bond strength (initial bond strength) was measured using a universal testing machine (Shimadzu Corporation Autograph) at a crosshead speed of 2 mm / min. The measurement was carried out within about one day after the sample for bond strength measurement was taken out of the water. For each Example and Comparative Example, the measured values of four samples were averaged to obtain the measurement result.
[0070] Furthermore, to examine the adhesion durability, for the other test group, each sample was subjected to 3,000 thermal cycles in which it was alternately immersed in constant temperature water baths of 5°C and 55°C for 1 minute each to prepare samples for measuring adhesion durability, and the tensile adhesion strength (adhesion strength after durability test) was measured in the same manner as above.
[0071] (2) Coating evaluation The bovine front teeth extracted within 24 hours after slaughter were polished with water-resistant abrasive paper P600 under water injection, and the dentin plane was scraped off so that it was parallel to the labial surface and flat. The dental adhesive prepared in each Example and Comparative Example was applied to this dentin plane, and air-blown for 5 seconds to dry it. The adhesive layer after air-blown was visually observed to confirm whether a coating was formed. When a good coating was formed, it was rated as "good", when a coating sufficient as an adhesive composition was formed, it was rated as "fair", and when the coating was insufficient or the coating properties were poor, it was rated as "no good".
[0072] 3. Examples and Comparative Examples Example 1 (1) Preparation of dental adhesive composition: 2g of MDP, 2.5g of HEMA, 3.3g of BisGMA, 2.2g of 3G, 12.8g of acetone, 2g of DM-30, and 0.02g of V1 were mixed to obtain the first agent. In addition, 1g of water, 8g of ethanol, 0.05g of EC, 0.2g of PO1, and 0.3g of B1 were mixed to obtain the second agent.
[0073] (2) Adhesiveness evaluation: The dental adhesive composition obtained in (1) was used as an adhesive, and the above-mentioned adhesiveness evaluation was carried out. The results of using the composition immediately after preparation showed that the adhesive strength to dentin was 18.2 MPa at the initial stage and 16.4 MPa after 3000 thermal cycles, both of which show high adhesive strength. The adhesive strength to porcelain was also high, being 20.1 MPa at the initial stage and 18.5 MPa after thermal cycles. Furthermore, when the composition was used after storing at 50°C for 2 weeks, the adhesive strength to dentin was 17.8 MPa at the initial stage and 16.0 MPa after thermal cycles. The adhesive strength to porcelain was 19.5 MPa at the initial stage and 18.1 MPa after thermal cycles. Since the dental adhesive composition of the present invention showed good adhesive strength even after storing at 50°C for 2 weeks, it can be said that the dental adhesive composition of the present invention has excellent storage stability. In addition, the result of the film observation test was also "good".
[0074] Examples 2 to 25 Except for changing the ratio of each component as shown in Tables 1 and 2, adhesive compositions were prepared in the same manner as in Example 1, and the obtained compositions were used as adhesives to evaluate adhesion and performance. The results are shown in Table 3. As shown in Table 3, all of the Examples show high adhesive strength both initially and after storage. Furthermore, film formation is also good. In the table, "↑" means "same as above," and the numbers in parentheses after each component show the amount (parts by mass) of the component.
[0075] [Table 1]
[0076] [Table 2]
[0077] [Table 3]
[0078] Comparative Examples 1 to 19 Adhesive compositions were prepared in the same manner as in Example 1, except that the ratio of each component was changed as shown in Table 4. The adhesive properties of the resulting compositions were evaluated. The evaluation results are shown in Table 5.
[0079] [Table 4]
[0080] [Table 5]
[0081] As shown in Table 5, in Comparative Example 1 which did not contain component (a1), the adhesive strength to tooth tissue was low because no adhesive component to tooth tissue was contained. In Comparative Example 2, which contained the (a1) component in the second agent, and Comparative Example 14, which contained the (d2) component in the second agent, the storage stability of the (B) component was poor, and therefore the adhesive strength to porcelain after 2 weeks at 50°C was low. In Comparative Example 3, which did not contain component (C), and Comparative Example 4, which contained less than 20 parts by mass of component (C), the tooth surface was insufficiently demineralized, and the adhesive strength to dentin was reduced. In addition, because the concentrations of each component were high, the viscosity of the composition was high even before air blowing, making it difficult to apply evenly. Accordingly, each adhesive strength also showed a low value. In Comparative Example 5, where the content of component (C) exceeded 250 parts by mass, the adhesive strength decreased due to the low content of the adhesive component, and the concentration of component (D) was low, resulting in insufficient film formation. In Comparative Example 6, which did not contain the component (c1), and Comparative Example 7, where the component (c1) was less than 5 parts by mass, demineralization of the tooth surface did not progress, and therefore the adhesive strength to dentin was low. In Comparative Example 8, in which the content of component (c1) exceeded 30 parts by mass, the water could not be completely removed by air blowing, the film formation was insufficient, and the adhesive strength to dentin was reduced. In Comparative Example 9, in which the second part did not contain the component (c2), the solubility of the component (d1) decreased, and a homogeneous second part could not be prepared.
[0082] In Comparative Example 10, which did not contain component (B), and Comparative Example 11, in which the content of component (B) was less than 0.5 parts by mass, the adhesive strength to porcelain decreased. In Comparative Example 12, in which the content of component (B) exceeded 20 parts by mass, the storage stability was reduced due to the high concentration of component (C), and the adhesive strength to porcelain after storage at 50° C. for 2 weeks was low. In Comparative Example 13, which did not contain the (d1) component, and Comparative Example 16, in which the content of the (d1) component was less than 0.05 parts by mass, the formation of the coating was insufficient, and the adhesive strength also showed a low value accordingly. The component (d1) did not contain the organic polymer-based coating strengthening agent of the present invention, and instead, the organic polymer PMMA was used as the coating strengthening agent for the second agent (in Comparative Example 15, a uniform second agent could not be prepared because PMMA was not soluble in ethanol). In Comparative Example 17, in which the content of component (d1) exceeded 3 parts by mass, the composition had a high viscosity even before air blowing, making it difficult to apply evenly. Accordingly, each adhesive strength also showed a low value. In Comparative Examples 18 and 19, in which the organic polymer-based coating strengthening agent d3, whose solubility in water is 0.1 g / 100 g water, was used, the water could not be completely removed by air blowing, and the coating formation was insufficient. Accordingly, each adhesive strength also showed a low value.
Claims
1. Polymerizable monomer component containing an acidic group-containing polymerizable monomer: 100 parts by mass, Water: 5 to 30 parts by mass, ethanol: 10 to 295 parts by mass, and contains 0.05 to 3 parts by mass of an organic polymer-based coating reinforcement agent consisting of an alkyl cellulose in which the -OH groups in the cellulose molecule are substituted with a group: -O-R and / or a group: -O-C(=O)-R, (wherein R in these groups is an alkyl group having 1 to 5 carbon atoms), and which has a solubility in water of 0.1 (g / 100 g-solvent) or less and a solubility in ethanol of 1 (g / 100 g-solvent) or more at 25°C; A dental adhesive composition comprising:
2. 2. The dental adhesive composition according to claim 1, wherein the alkyl cellulose is a polymer compound or polymer composition having a molecular weight distribution in which the content of components having a molecular weight of 140,000 or more is 20% or more.
3. The dental adhesive composition according to claim 1, further comprising 0.5 to 20 parts by mass of a silane coupling agent.
4. 2. The dental adhesive composition according to claim 1, further comprising: 1 to 50 parts by mass of an inorganic coating reinforcing agent.
5. Polymerizable monomer component (A) consisting of an acidic group-containing polymerizable monomer (a1) and an acidic group-free polymerizable monomer (a2): 100 parts by mass, Silane coupling agent (B): 0.5 to 20 parts by mass, A solvent component (C) including water (c1): 5 to 30 parts by mass and ethanol (c2): 10 to 295 parts by mass: 30 to 250 parts by mass; a coating reinforcement agent (D) of 0.05 to 53 parts by mass, including an organic polymer-based coating reinforcement agent (d1) of alkyl cellulose in which the -OH groups in the cellulose molecule are substituted with a group -O-R and / or a group -O-C(=O)-R, (wherein R in these groups is an alkyl group having 1 to 5 carbon atoms), and the alkyl cellulose has a solubility in water of 0.1 (g / 100 g-solvent) or less and a solubility in ethanol of 1 (g / 100 g-solvent) or more at 25°C; and A dental adhesive composition comprising: 0.01 to 20 parts by mass of a polymerization initiator (E) composed of a single or multiple components.
6. A kit comprising a first agent and a second agent packaged separately from each other, the kit being capable of preparing the dental adhesive composition according to claim 5 by mixing the two agents, The kit is characterized in that the first agent and the second agent are composed of a first composition and a second composition, respectively, having compositions determined by allocating each component defined in the composition based on the composition of the dental adhesive composition to be prepared, so as to satisfy the conditions shown in (1) to (4) below. Ingredient allocation conditions: (1) The polymerizable monomer component (A) is contained only in the first agent. (2) The silane coupling agent (B) is contained only in the second agent. (3) Regarding the solvent component (C), the ethanol (c2) is contained only in the second agent or in both the first agent and the second agent, and other components are contained in the first agent and / or the second agent. (4) The organic polymer-based coating strengthening agent (d1) is contained in either one or both of the first and second agents.
7. The dental adhesive composition to be prepared further comprises 1 to 50 parts by mass of an inorganic coating strengthening agent (d2) as a coating strengthening agent (D), and the inorganic coating strengthening agent (d2) is contained only in the first agent. The kit according to claim 6.
Citation Information
Patent Citations
Means for pulverizing waste material different in shape
JP1978095362A
Three-way dump truck
JP1983008447A
Dental adhesive composition
JP1988250310A
Composition for dental use
JP2000128723A
Dental oxygen blocking material
JP2004284969A